Calculation model including time-varying coefficients for calculating the lateral pressure of bottom-up pumping self-compacting concrete. (10th January 2022) - Zhang, Wenxue; Lu, Xiangtao; Fang, Rong; Zhao, Xu
Highlights: A tailored calculation model for predicting lateral pressure was proposed. The time-varying characteristics of two key coefficients were considered. A new test device was designed to study the time-varying characteristics. The application of two demold agents was considered in experiment. Two field tests had done for verifying the accuracy of the calculation model. Abstract: The accuracy of concrete lateral pressure predictions affects the safety and economic aspects of constructions. For the prediction of the maximum lateral pressure of bottom-up pumping self-compacting concrete, based on the graph multiplication method, a calculation model with time-varying coefficients was proposed, which considers the friction effect. The time-varying characteristics of the key coefficients of self-compacting concrete with slumps of 600 mm, 700 mm, and 800 mm were studied by simulating the concrete pouring process and, then, applied to the calculation model. In two dumbbell-shaped steel arch bridges, pressure sensors were placed in the inner wall of the typical steel pipe's section to measure the lateral pressure during the pumping process and, hence, verify the accuracy of the calculation model. The applicability of the calculation model was verified by comparing the calculated results with other specifications. Results indicate that, as the liquid level increases, the effect of friction will cause a significant increase of pressure at the bottom. In predicting the maximum lateral pressure of bottom-up pumping self-compacting concrete, the calculation model can be well applied in the case where the liquid level was higher.